PENGARUH KUALITAS SUMBER DAYA MANUSIA TERHADAP PRODUKTIFITAS KERJA PEGAWAI KELURAHAN RUFEI DI KOTA SORONG - Fransin Benjamin; Lili Sarce Joi Sapari; Ade Andriani Renouw (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine whether there is an influence or not the effect of the quality of human resources on the work productivity of employees in the Rufei Village, using a simple linear regression analysis technique, with a total sample of 85. And the results of the research are that the data used in this research are valid and reliable. This can be seen from the results of the validation test where all Sig. (Significant) value less than 0.05 and Cronbach's Alpha value greater than 0.06 so that the data used can also be said to be reliable. Then for Simple Linear Regression Analysis the equation is obtained: Y = 9.561 + 0.268 X, this equation means that the variable quality of human resources has a positive influence, this means that if the independent variable variable (X) the quality of human resources has increased by 1%, then variable dependent variable (Y) work productivity increased by 0.268. Then a T (Partial) test was carried out to find out whether the effect given by Simple Linear Regression Analysis was significant. Based on the results of the analysis, the value of Sig. (Significant) 0.000 <0.05 and t count 2.641 > 1.667 then the hypothesis H0 is rejected and Ha is accepted, which means that there is an influence between the independent variable (X) the quality of human resources on the dependent variable (Y) work productivity